Exploring the role of pyroptosis in the pathogenicity of heart disease - Bhatti, Rohail; Sato, Priscila Y. (Frontiers in Physiology, 2024)
Cell death is an essential cellular mechanism that ensures quality control and whole-body homeostasis. Various modes of cell death have been studied and detailed. Unbalanced cell death can lead to uncontrolled cell proliferation (i.e. tumors) or excessive loss of cells (i.e. ischemia injury tissue loss). Thus, it is imperative for modes of cell death to be balanced and controlled. Here, we will focus on a recent mode of cell death called pyroptosis. While extensive studies have shown the role of this route of cell death in macrophages and monocytes, evidence for pyroptosis have expanded to encompass other pathologies, including cancer and cardiac diseases. Herein, we provide a brief review on pyroptosis and discuss current gaps in knowledge and scientific advances in cardiac pyroptosis in recent years. Lastly, we provide conclusions and prospective on the relevance to various cardiac diseases.